Pembaharuan Pemikiran Islam di Timur Tengah dan Asia Selatan serta Pengaruhnya terhadap Kemerdekaan Negara-Negara Islam - Hadziq, Muhammad Fadhil; Muzadi, Narul Hasyim (Adabuna : Jurnal Pemikiran dan Pendidikan, 2025)
The reform of Islamic thought in the Middle East and South Asia emerged as a response to colonialism and the challenges of modernity. Figures such as Jamaluddin Al-Afghani, Muhammad Abduh, Rashid Rida, Hassan Al-Banna, Sayyid Ahmad Khan, Abul A'la Maududi, Ali Shariati, and Muhammad Ali Pasha initiated religious reforms that significantly influenced the struggle for independence in the Islamic world. However, comparative studies on their contributions to independence movements in these two regions remain limited. This study aims to analyze the ideas of key Islamic reformers and examine their relevance in addressing contemporary challenges. Using a qualitative historical approach, this research explores how these reformers integrated Islamic teachings with modern advancements in education, governance, and law to resist colonialism. The findings show that Islamic reformers played a crucial role in shaping nationalist movements, reviving Islamic identity, and supporting the establishment of independent Muslim nations. Their advocacy for education, ijtihad (independent reasoning), and political unity formed the foundation of anti-colonial resistance. In conclusion, Islamic thought reform not only contributed to national independence but also continues to influence contemporary Islamic governance and social movements. This study offers valuable insights into the dynamic relationship between Islam, modernization, and political independence, and provides a basis for further research on the relevance of Islamic reformist thought in the modern era.